Isolation and Screening of Potential Cellulolytic and Xylanolytic Bacteria from Soil Sample for Degradation of Lignocellulosic Biomass - Bhupal Govinda Shrestha; Sanjaya Ghimire; Shakep Bhattarai; Sailesh Phuyal; Bimal Thapa (Journal of Tropical Life Science, 2016)
Cellulolytic/Xylanolytic microorganisms such as bacteria and fungi are accountable for conversion of lignocellulosic biomass in soil. Despite this vast number of cellulose/xylanase producers, there is a deficiency of microorganisms that can produce a significant amount of cellulase/xylanase enzyme to proficiently degrade cellulose/xylan to fermentable sugars. Although bacteria have extremely high natural diversity, which bestowsthem with the aptitude to produce stable enzymes, little emphasis has been given to cellulose/xylanase production from bacteria. Seven soil samples were collected from eastern hilly districts of Nepal viz. Taplejung, Panchthar and Sankhuwasabha districts, from soil surface and at depth of 10cm to 20cm, and were isolated separately. From the seven soil samples, four bacterial isolates were obtained. Isolates (PSS, P1D, TLC, SNK) were then screened for cellulolytic/xylanolytic activity using Congo red assay on Carboxymethylcellulose (CMC)/xylan agar plates. The enzyme activity obtained from isolates was dependent on substrate concentration. The activity of enzymes produced by isolates were also measured and compared on pretreated sugarcane bagasse. Among those samples, the greatest zone of inhibition in both CMC (1.3 cm) and xylan (1.0 cm) agar media was seen in isolate P1D. It also produced the highest activity of endoglucanase and xylanase i.e. activity 0.035 U/mL and 0.050 U/mL respectively at 0.010 mg mL-1 standard substrate concentration of CMC and xylan.Â